Procesy koncentracji w polskim sektorze bankowym - Kacperska, Elżbieta; Kraciuk, Jakub (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2004)
The financial sector presents the strongest tendency towards capital concentration, what is the effect of its deregulation, liberalization and strong competitiveness. Fusions and foreign investors, who are taking banks over, are accomplishing this concentration. From the beginning of 1993 until the first quarter of 2004, the number of active commercial banks decreased from 87 to 59 and 27 fusions and assumptions were noticed. At the beginning of 2004 foreign investors controlled 46 commercial banks out of 59 operating in Poland. The value of their investments exceeded 7 .2 billions PLN and they owned 76.3% of equity and supplementary funds and 67.4% of assets. Owing to these investments, the banking sector development has started and the investors subsidised existing banks, improved infrastructure and made many innovations. The large foreign banks, which were set up as a result of concentration, made banking system more effective and facilitated development of national economy. On the other hand, the superior contribution of large foreign banks obstructs national financial policy and makes the financial sector sensitive to prosperity fluctuations and a crisis of the world banking system.